Brooks Range Treeline White Spruce Needle Length and Mass per Area (2019-2022) ... - Sullivan, Patrick; Hewitt, Rebecca; Maher, Colin; Dial, Roman (NSF Arctic Data Center, 2023)
Measurements of treeline white spruce needle length and needle mass per unit projected needle area on needles produced and sampled 2019, 2021 and 2022. Measurements of needle length and projected area were made using WinSeedle software on scans of the needle samples. The purpose of of this dataset was to examine spatial variation in treeline white spruce needle attributes across the Brooks Range and in relation to local microclimates. ...